Hubungan Pengetahuan Ibu dengan Kelengkapan Imunisasi Dasar pada Balita Usia 1-5 Tahun - Teti Rahmawati; Multi Agustin (Universitas Faletehan, 2021)
Immunization is an effort to increase the body's immunity against infectious diseases, can be passive or active immunity which is used as a prevention that has succeeded in reducing the infant and child morbidity and mortality. The purpose of this study was to determine the relationship between maternal knowledge and complete basic immunization in 1 to 5 year children. This study used analytical survey method with a cross sectional approach. The population were mothers who had children aged 1-5 years and lived in Lingkungan 01 RW 03 Ciriung Village. The samples were selected by using simple random sampling technique with the sample size of 95 toddlers. The data collection used a questionnaire, while the analysis used chi square Fisher's exact test (α=0.05). The results of the univariate analysis showed most respondents were categorized as early adulthood (88.4%), family income < minimum wage (54.7%), their education background ≤ senior high school (86.3%), had positive attitude (53.7%), received complete immunization (94.7%), and had good knowledge (92,6%). The results of the bivariate analysis showed a relationship between maternal knowledge and complete basic immunization in 1 to 5 year children with p value = 0.002. The recommendations of this study were to provide health education about immunization and conduct research using correlational study method.